2014
DOI: 10.11648/j.avs.20140205.13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Viral Antigens in Cattle Lung Tissues by Direct ELISA

Abstract: Abstract:Bovine Respiratory Disease is one of the most important diseases with serious financial losses for the cattle industry in worldwide. The aim of this study was to detect the associations between respiratory viruses; bovine herpes virus 1, bovine viral diarrhea virus, bovine respiratory syncytial virus, and Para influenza virus 3 statuses of a herd and bovine respiratory disease occurrence. Present study describes virological distribution of bovine respiratory viruses in nonvaccinated cattle (for mentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…BPIV3 and BRSV were detected by other researchers with serological and virological methods in cases of lower respiratory tract infections in cattle in Turkey (2, 6, 41). However, these studies were not performed by molecular methods and did not include genetic characterisation as we have done.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…BPIV3 and BRSV were detected by other researchers with serological and virological methods in cases of lower respiratory tract infections in cattle in Turkey (2, 6, 41). However, these studies were not performed by molecular methods and did not include genetic characterisation as we have done.…”
Section: Discussionmentioning
confidence: 80%
“…Data on virological detection of these agents in Turkey is limited (2, 6), but there are more studies on seroprevalence of these viruses among cattle herds. The studies reported lowest and highest seropositivity of 11% (1) and 92.8% (13) for BPIV3 and 28% (1) and 94% (13) for BRSV.…”
Section: Introductionmentioning
confidence: 99%
“…BoHV-1 positivity was found as 2% in 250 camel lung samples in a study via antigen ELISA (43). It has been reported that no positivity was detected in lung samples of 24 cattle in antigen ELISA study performed to determine BoHV-1 in Turkey (44). So, in the light of the examined literature, the present study is the first study to detect BoHV-1 positivity from cattle lung tissues by antigen ELISA method.…”
Section: Discussionmentioning
confidence: 58%
“…However, Masot et al (1993) considered ELISA as a diagnostic tool and most suitable technique for identifying BRSV antigen in the lung tissue. The detection of viral antigen from pneumonic lung tissue also tried by Avci et al (2014) by antigen capture direct ELISA and 16.6% positivity recorded for BRSV antigen whereas could not find presence of BoHV-1, BPI3V and BVDV.…”
Section: Detection Of Respiratory Viral Antigens In Nasal Swabs Of Bo...mentioning
confidence: 99%
“…Bovine Parainfluenza-3 virus (BPI3V) is also associated with respiratory infections, characterized by rhinitis, acute and silent fever nasal secretions (Solis-Calderon et al, 2003) (Fulton and Confer 2012). However ELISA has been test of choice for detection of antigen and antibody due to advantage to perform this test within a short time frame in the laboratory and is more efficient in the differential diagnosis as combined infection can also be detected simultaneously for different associated viral agents (Avci et al, 2014). The present study planned to detect the various respiratory viral antigens in nasal excretions of cattle and buffaloes and determine the BRD occurrence by sandwich ELISA.…”
Section: Introductionmentioning
confidence: 99%